Security strategies for cloud identity management - a study - Chunduru, Anilkumar; S, Sumathy (International Journal of Engineering and Technology, 2018)
Emphasis on security for providing Access Control in Cloud computing environment plays a significant role. Cloud computing provides number of benefits such as resource sharing, low speculation and large storage space. Huge amount of information stored in cloud can be accessed from anywhere, anytime on pay-per use basis. Resources in cloud should be accessed only by the authorized clients. Access Control in cloud computing has become a critical issue due to increasing number of users experiencing dynamic changes. Authentication, authorization and approval of the access ensuring liability of entities from login credentials including passwords and biometric scan is essential. Also, the federated authentication management is secured. Current approaches require large-scale distributed access control in cloud environment. Data security and access control are the drawbacks in existing access control schemes. Due to the drawbacks in existing access control schemes such as privacy of information when susceptible information is stored in intermediary service provider a federated identity access management is essential. Access control applications majorly concentrate on Healthcare, Government Organizations, Commercial, Critical Infrastructure and Financial Institutions. This review illustrates a detailed study of access control models in cloud computing and various cloud identity management schemes.